Using Brief Experimental Analysis to Identify Effective Early Reading Interventions - Quick, Jessa B. (My University, 2018)
The National Center for Educational Statistics in 2015 found that only thirty-six percent of fourth-grade and thirty-four percent of eighth-grade students performed at or above the proficient level in reading. These students do not have the skills necessary to support them in their education. Research has shown that BEA can be used to identify effective reading fluency interventions for struggling students and that these interventions can be effective when implemented across time (e.g., Eckert et al., 2002, Daly et al., 1999). Only one study to date (Petursdottir et al., 2009) has studied the ability of BEA to identify early reading interventions. The present study examined the use of BEA in identifying effective early reading interventions. Three students entering 1st and 2nd grade were invited to participate in the study occurring over the summer months. BEA procedures were used to identify an intervention strategy for each student. The three intervention strategies assessed were repeated reading, modeling, and goal setting and incentive. Progress was measured bi- weekly using FAST probes in letter sound fluency, decodable word fluency, and oral reading fluency. The results from the study suggest that BEA identified intervention strategies did improve reading performance for all three students.
Keywords: Brief experimental analysis (BEA); Reading--Remedial teaching; Oral reading--Study and teaching; Reading (Elementary)